Graphene/graphitic carbon nitride decorated with AgBr to boost photoelectrochemical performance with enhanced catalytic ability. (30th September 2020) - Muhmood, Tahir; Cai, Zihe; Lin, Shengxuan; Xiao, Jiajia; Hu, Xiaobin; Ahmad, Farooq
Abstract: A novel graphene nanoplatelets (GNP) bridge between two semiconductors (AgBr and graphitic carbon nitride) was created to boost photoelectrochemical performance. The heterojunction created makes the whole system a Z-scheme catalyst. For the construction of this catalyst, the syringe pump methodology was adopted and different analytical techniques were used for the confirmation of structure and morphology. High angle annular dark field (HAADF), dark field (DF), DF-4 and DF-2 techniques, using Z-contrast phenomena, confirmed the heterostructure (ABGCN) and its composition. The constructed structure showed an enhanced photoelectrochemical and catalytic property against 'acute toxicity category-III (MM)' and 'category-IV (tetracycline hydrochloride (TH))' organic pollutants. The constructed catalyst degraded the MM in 57 min and the TH in 35 min with degradation rates of 0.01489 min −1 and 0.02387 min −1, respectively, due to the accumulation of photogenerated electrons on the conduction band (CB) of g-C3 N4 and photogenerated holes on the valence band (VB) of AgBr by the transformation of charges through the graphene bridge. An ion trapping study also revealed that ·O2 and h + were the active species which actively participated in the photocatalytic reaction.